Laboratory Measurements of Gravel Thermal Conductivity: An Update Methodological Approach. (September 2017) - Santa, Giorgia Dalla; Peron, Fabio; Galgaro, Antonio; Cultrera, Matteo; Bertermann, David; Mueller, Johannes; Bernardi, Adriana
Abstract: Direct measurements of gravel thermal properties are usually quite challenging to be performed in laboratory, due to the very coarse sediments size. As a consequence, the reference thermal values provided by literature for gravels are quite limited and dispersed. A guarded hot plate Taurus Instruments TLP 800, usually used for measuring the thermal conductivity of buildings materials, was slightly modified in order to measure the thermal conductivity of some gravel samples. The tests were performed both in dry and wet conditions. The paper presents the first obtained results.